An unsafe behaviour formation mechanism based on risk perception. Issue 2 (9th September 2018) - Huang, Lang; Wu, Chao; Wang, Bing; Ouyang, Qiumei; Lin, Huanhuan
Abstract: It is commonly acknowledged that human behaviour is implicated in most safety problems. However, research on the formation mechanism of unsafe behaviour remains incomplete. Risk perception is one of the fundamental issues in risk research, and individual risk perception can be identified as a critical antecedent of human behaviour. This study attempts to construct and test a theoretical model to reveal the formation mechanism of unsafe behaviour based on risk perception. First, to lay a solid foundation for the developed new mechanism, several key concepts about risk perception and unsafe behaviour were explained. Second, the formation mechanism of biases in individual risk perception was developed based on psychological distance theory, and the biases in risk perception were subsequently classified. Lastly, an unsafe behaviour formation mechanism was put forward based on risk perception as an explanatory variable. This study is novel in that it uses psychological distance to explore the formation of biases in individual risk perception. Further, the presented work provides a new approach to understanding and explaining the formation mechanism of human unsafe behaviour.